Efektivitas Psikoedukasi Untuk Meningkatkan Pengetahuan Ibu Tentang Masalah Perilaku Makan Anak di Kelas Ibu Balita - Lestyasari, Bintang; Meiyuntariningsih, Tatik (LPPM Institut Pendidikan Nusantara Global, 2025)
The toddler period is a crucial stage in shaping eating behavior that significantly affects children’s health. The phenomenon of picky eating or selective eating habits often occurs due to inconsistent parenting and mothers' limited nutritional knowledge. This study aims to analyze eating behavior among toddlers and evaluate the effectiveness of psychoeducation in improving mothers’ understanding within family health posts (posyandu). This research employed a quantitative method with a one-group pretest–posttest design involving 31 mothers with children aged 4–5 years from three family health posts under Puskesmas S, Surabaya. Data were collected through the Children Eating Behavior Questionnaire (CEBQ), psychoeducation sessions, observation, and interviews with midwives and nutritionists. The results indicate that most children exhibited irregular eating patterns and food selectivity. Psychoeducation improved mothers’ knowledge of healthy eating practices, though still at a moderate level. The program proved effective as a promotive and preventive effort to establish healthy eating habits from an early age.